Analysis Of The Effect Of Financial Ratios On The Profit Sharing Rate Of Mudharabah Savings In Islamic Commercial Banks In Indonesia For The 2015-2020 Period - Imbi Dewandari; Fuad Hasyim; Dian Rachmawati (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2023)
This study aims to analyze the effect of financial ratios consisting of the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), BOPO and Financing of Deposit Ratio (FDR) on the profit-sharing rate of mudharabah savings at Islamic Commercial Banks in Indonesia for the 2015-2020 period. The population in this study is all Sharia Commercial Banks registered with the Financial Services Authority (OJK) in 2015-2020. The sample was obtained from 11 Sharia Commercial Banks selected using the purposive sampling technique. This type of research is quantitative, using data analysis methods in the form of linear regression analysis of data. The results of this study show that CAR, BOPO, and FDR have no effect on the profit-sharing rate of mudharabah savings at Sharia Commercial Banks in Indonesia from to 2015-2020 period. Meanwhile, NPF affects the profit-sharing rate of mudharabah savings in Islamic Commercial Banks in Indonesia during the 2015-2020 period.